Multiobjective Differential Evolution Clustering Algorithm Based on Multimedia Information in Working Mechanism Innovation for Traditional Chinese Medicine. (8th October 2022) - Zhu, Xiaoling; Cheng, Hongsheng; Zhang, Xu; Zhu, Huaxu; Sun, Zhiguang
Abstract : Aiming at working mechanism innovation for traditional Chinese medicine, a multiobjective differential evolution clustering algorithm based on multimedia information is proposed and applied. In promoting the international development of the traditional Chinese medicine industry, R&D innovation and working mechanism innovation must be paid attention to. This paper takes a specific Chinese medicine company as an example, combined with differential evolution clustering algorithm to effectively help Chinese medicine enterprises choose a more suitable innovation model. This paper starts with specific cases and carries out research from the microperspective of traditional Chinese medicine enterprises. It believes that in the process of international development, traditional Chinese medicine enterprises must base on overseas investment in R&D and innovation, strengthen self-help innovation, further enhance their R&D stamina through working mechanism innovation, gradually open overseas markets, and realize the internationalization of traditional Chinese medicine.